DECONSTRUCTION OF CRIMINAL PUNISHMENT FOR CHILDREN: A PHILOSOPHICAL, LEGAL, AND SOCIOLOGICAL STUDY - Aji Mulyana; Iip Saripudin; Chepi Ali Firman Zakaria; Kayla Andini Putri; Ajeng Permana (Proceeding International Conference on Social Sciences, 2026)
The criminalisation of children in conflict with the law still leaves many issues unresolved because law enforcement practices are not yet fully aligned with the principle of child protection, which treats children as individuals in the process of development. The high rate of juvenile delinquency in Tasikmalaya and Cianjur shows that juvenile crime is a multidimensional issue with internal factors such as family dysfunction, trauma, and weak self-control, as well as external factors such as a permissive social environment, peer influence, and structural pressure. This study aims to deconstruct the paradigm of child punishment through philosophical, juridical, and sociological analysis to assess the suitability between the ideal values of the SPPA Law and its implementation in the field. The research method used a qualitative approach with a constructivist paradigm combined with a normative-empirical approach through regulatory review, literature study, case analysis, limited interviews, and field observations in Cianjur Regency and Tasikmalaya City. The results of the study reveal a discrepancy between the principle of restorative justice in the SPPA Law and the practice of punishment, which is still retributive in nature, influenced by a lack of rehabilitation facilities, a lack of understanding among officials, weak coordination between institutions, and other structural and cultural barriers. This study emphasises the need for comprehensive reform through strengthening diversion, providing child-friendly facilities, increasing the capacity of officials, and formulating regional policies based on restorative justice to realise sentencing that is oriented towards guidance, protection, and social reintegration of children.